Costa Rica : Request for Purchase Under the Rapid Financing Investment-Press Release; Staff Report; and Statement by the Executive Director for Costa Rica. (IMF Staff Country Reports; Country Report ;, 2020)
This paper states Costa Rica's Request for Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 pandemic has severely impacted Costa Rica with its large exposure to trade, tourism, and foreign direct investment. The global economic slowdown and the necessary containment measures have impacted growth and fiscal accounts and created an urgent balance of payments need. The IMF's emergency financing under the RFI is expected to help support urgently needed public health and social spending measures, while addressing the balance of payments need. It will also catalyze support from other multilateral agencies, which will be critical to addressing the remaining financing needs. The authorities have taken timely, well-targeted measures to mitigate the adverse effects of the pandemic. They introduced extensive containment measures, which have helped flatten the infection curve. In order to mitigate the economic and social impact of the crisis, they adopted a temporary moratorium on tax payments, social transfers to protect the most vulnerable, and monetary and regulatory measures to ease credit and liquidity conditions.